(untitled) (Web of Teachers: Inderscience Research, 2023)
This article discusses the role of educational technologies in the development of basic and linguistic competencies in the native language of 6th grade students, the importance of their application, the use of acquaintance technology to help students realize their abilities, overcome barriers to communication, and improve text analysis and communication skills.